1996
DOI: 10.1002/(sici)1097-4644(19960101)60:1<23::aid-jcb5>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

BCL‐2 family proteins: Regulators of cell death involved in the pathogenesis of cancer and resistance to therapy

Abstract: The BCL-2 gene was first discovered because of its involvement in the t(14;18) chromosomal translocations commonly found in lymphomas, which result in deregulation of BCL-2 gene expression and cause inappropriately high levels of Bcl-2 protein production. Expression of the BCL-2 gene can also become altered in human cancers through other mechanisms, including loss of the p53 tumor suppressor which normally functions as a repressor of BCL-2 gene expression in some tissues. Bcl-2 is a blocker of programmed cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
173
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 0 publications
2
173
0
2
Order By: Relevance
“…Evidence indicates that Bcl-2 and Bcl-XL act as stabilizers of mitochondrial membrane integrity by blocking the release of cytochrome c and subsequent caspase-9 and -3 activation, thus regulating the mitochondrial apoptotic pathway (Korsmeyer, 1992;Kluck et al, 1997;Martinou et al, 2000;Tsujimoto, 2000;. These effects comprise the main mechanism by which Bcl-2 and Bcl-XL inhibit the induction of apoptosis by a variety of chemotherapeutic agents hRFI enhances chemoresistance to 5-FU T Konishi et al including 5-FU (Miyashita and Reed, 1993;Reed et al, 1996;Nita et al, 2000;Sun et al, 2002;Violette et al, 2002). In compatible with this evidence, the present study has revealed that siRNA downregulation of either Bcl-2 or Bcl-XL prominently increases 5-FU-induced apoptosis, indicating that both Bcl-2 and Bcl-XL are crucial determinants of the apoptosis sensitivity towards 5-FU in HCT116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that Bcl-2 and Bcl-XL act as stabilizers of mitochondrial membrane integrity by blocking the release of cytochrome c and subsequent caspase-9 and -3 activation, thus regulating the mitochondrial apoptotic pathway (Korsmeyer, 1992;Kluck et al, 1997;Martinou et al, 2000;Tsujimoto, 2000;. These effects comprise the main mechanism by which Bcl-2 and Bcl-XL inhibit the induction of apoptosis by a variety of chemotherapeutic agents hRFI enhances chemoresistance to 5-FU T Konishi et al including 5-FU (Miyashita and Reed, 1993;Reed et al, 1996;Nita et al, 2000;Sun et al, 2002;Violette et al, 2002). In compatible with this evidence, the present study has revealed that siRNA downregulation of either Bcl-2 or Bcl-XL prominently increases 5-FU-induced apoptosis, indicating that both Bcl-2 and Bcl-XL are crucial determinants of the apoptosis sensitivity towards 5-FU in HCT116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In neuroblastoma bcl-2 expression seems to correlate with the morphology and differentiation of neuroblastoma cells in vitro, greater bcl-2 expression being associated with more neuroblastic cells (Reed et al, 1991). Studies in, for example, myeloid leukaemia, carcinoma of prostate and large cell Non Hodgkins lymphoma, have found bcl-2 expression to be associated with a poor response to treatment, and a shorter disease free and overall survival (Colombel, 1993;Reed et al, 1996). However, Silvestrini et al (1994), found bcl-2 expression to correlate with a good prognosis in breast cancer.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…However, Silvestrini et al (1994), found bcl-2 expression to correlate with a good prognosis in breast cancer. Reed et al (1996) discussed this paradoxical result, hypothesising that it is a reflection of the complex interaction between the family of genes which control apoptosis, and in particular the ratio of activity of the proapoptotic gene Bax to the anti apoptotic bcl-2. A decrease in the ratio of bcl-2 to Bax protein renders cells more vulnerable to apoptosis (Borner, 1996).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, results to date indicate that members of the Bcl-2 family of proteins play a prominent role in regulating intracellular thresholds to apoptotic cell death-promoting stimuli. 87 Bcl-2 functions as a negative regulator of apoptosis and has been reported to be overexpressed in Յ70% of breast cancers. 88 Furthermore, high levels of bcl-2 gene expression have been correlated with an increased resistance to therapeutic agents that activate both p53-dependent and -independent apoptotic signaling pathways.…”
Section: Bystander Effectsmentioning
confidence: 99%